A emergência do sujeito pedagógico surdo no espaço de convergência entre comunidade e escola de surdos - Camatti, Liane (2011)
The visibility achieved by deaf school, from the renitence of discourses that take deafness as a linguistic, cultural difference, has generated a scenario of permanent convergence between deaf school and community. This occurs due to the fact that the deaf community has found in the school space a trench that enables community articulations. Then, there are new possibilities of investigating practices delimitated by the symbolic space emerging from the intersection between school and community. This research attempts to understand the production of the pedagogical deaf subject in the convergence between the community and school spaces. In order to do that, the context of three cities in Rio Grande do Sul has been investigated: Caxias do Sul, Porto Alegre and Santa Maria, through discussions with deaf students and teachers participating in the deaf school and also acting as community leaders. Post-structuralist studies have provided the theoretical support for the analysis. The development of this study has allowed for a general perspective of the deaf community s moves from their cultural capital and the way it catalyzes possibilities of resistance. The deaf school, taken with great positivity, has been constituted as a privileged space of constitution of specific ways of being deaf. The community has been inserted into the school aiming at recursively investing in the formation of a political profile of the deaf who are subject to pedagogization in that school, with the purpose of guaranteeing the maintenance of the very community.